How rootstocks influence salt tolerance in grapevine?. The role of conferred vigor and ionic exclusion - Vila, Hernan Felix (2016)
The aim of this work was to evaluate whether selected grapevine rootstocks can confer greater salt tolerance than own-rooted Vitis vinifera L. A trial was carried out with potted own-rooted 'Malbec' vines and also grafted onto three rootstocks (101-14 Mgt, 1103P and Cereza). Aditionally, the vines were irrigated with a solution containing 0, 50 and 100 mM NaCl. Vegetative growth was the most sensitive variable to salinity and was affected even at 50 mM. Above 0.1% dw Na+ and 0.6% dw Cl-, the leaf area was negatively correlated with Na+ and Cl- in leaf blades. Membrane integrity and chlorophyll content in leaves were affected only at 100 mM. At 50 mM, 1103P showed a decrease in leaf area but this parameter was not further affected at 100 mM. Own-rooted and 1103P vines showed fewer visual symptoms of toxicity and maintained higher leaf area (+450% higher relative to 101-14 Mgt) and higher membrane integrity (+81% higher relative to Cereza) at high salinity. Own-rooted and 1103P vines grown in 0 mM NaCl also showed higher leaf area and biomass production (i.e., vigor), suggesting that salt tolerance is linked to innate vigor. Regardless of the NaCl content, 101-14Mgt showed higher Na+ concentration in leaf blades than own-rooted and 1103P vines (+266%). At 50 mM, Cereza concentrated more Cl- than the others (+114%). At 100 mM, Cereza and 101-14 Mgt concentrated more Cl- than both 1103P and own-rooted vines (+133%). The 1103P limited the entry of Na+ and Cl- to the vines more than the others (-58 and -62% respectively), suggesting a higher exclusion capacity. The results suggest that the use of own-rooted 'Malbec' remains as a viable alternative under high soil salinity conditions. The use of the 1103P rootstock also appears as an alternative due to its excluding behavior.